El legado de Spinoza (2019)
This essay by Richard Rorty is built upon a fundamental thesis: that Spinoza started a philosophical tradition which eventually would end on pragmatism. The superation of cartesian dualism by the means of understanding body and mind as parts of the same unity allows a certain realization of the world that finally enables us to question: which is the nature of truth?